The relationship of soil-moisture saturation and time-lapse static shifts-An example from the Ketzin pilot site - Bergmann, P.; Ivandic, M.; Kashubin, A.; Lüth, S.; Ivanova, A.; Juhlin, Christopher (EAGE Publishing BV, 2014)
Changes in the near surface are a major problem for land time-lapse seismic projects. Three seismic surveys at the Ketzin pilot site for CO2 storage in Germany demonstrated the importance of removing the variations in the shallow subsurface by applying spatially variable, relative time shifts to the different vintages prior to 4D interpretation. The main reason for these time shifts is a change in seismic velocities in the ground layer above the water table due to different soil-moisture saturation at the times of acquisition. We compared the variation in precipitation, groundwater level and trace-to-trace time shifts between the baseline and two monitor surveys and revealed that delays in reflected energy are in a qualitative sense, proportional to the moisture content in the soil.